Presence and extent of the primary health care attributes among children hospitalized for pneumonia - Juliana Coelho Pina; Suzana Alves de Moraes; Maria Cândida de Carvalho Furtado; Débora Falleiros de Mello (Universidade de São Paulo, 2015)
OBJECTIVE: to analyze the presence and extent of the primary health care attributes among children hospitalized for pneumonia.METHOD: observational and retrospective study with hospital-based case-control design, developed in three hospitals associated to the Brazilian Unified Health System, located in a city of the State of São Paulo, Brazil. The study included 690 children under five years old, with 345 cases and 345 controls.RESULTS: both groups scored high for access to health services. In contrast, high scores for attributes such as longitudinality and coordination of care were observed for the controls. Despite low scores, integrality and family counseling were also high for the controls.CONCLUSION: knowledge of the aspects involving the primary health care attributes and its provision for child care are very important because they have the potential to support professionals and managers of the Brazilian Unified Health System in the organization of health services.